2007
DOI: 10.1677/joe-07-0568
|View full text |Cite
|
Sign up to set email alerts
|

Heads or tails? Stressor-specific expression of corticotropin-releasing factor and urotensin I in the preoptic area and caudal neurosecretory system of rainbow trout

Abstract: Corticotropin-releasing factor (CRF)-and urotensin I (UI)-expressing cells of the preoptic area (POA) and caudal neurosecretory system (CNSS) are considered key contributors to the regulation of the stress response in fish; however, the expression pattern of these neurons to environmental and social challenges have not been compared in a single study. Therefore, we characterized in rainbow trout (Oncorhynchus mykiss) the central distribution of CRF and UI expression and quantified the POA and CNSS mRNA levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 50 publications
5
74
1
2
Order By: Relevance
“…Fork length and BW were then recorded, and several tissues were collected to quantify the mRNA levels of key appetite-and growth-regulating genes by quantitative real-time RT-PCR (qRT-PCR) or tissue metabolite levels. The brain was removed and regionally dissected (Bernier et al 2008) to isolate the POA and the hypothalamus. Whole pituitary and liver, and a standardized sample of white muscle (rostral to dorsal fin) were also collected.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Fork length and BW were then recorded, and several tissues were collected to quantify the mRNA levels of key appetite-and growth-regulating genes by quantitative real-time RT-PCR (qRT-PCR) or tissue metabolite levels. The brain was removed and regionally dissected (Bernier et al 2008) to isolate the POA and the hypothalamus. Whole pituitary and liver, and a standardized sample of white muscle (rostral to dorsal fin) were also collected.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…After development of the radiographs, the number of steel beads in the gastrointestinal tract was tallied and the amount of feed consumed calculated using a calibration curve. Plasma analyses Plasma cortisol concentrations were measured in triplicate by RIA as per the methods of Bernier et al (2008). The lower detection of the assay was 16 pg/ml.…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…The brain, whole pituitary and liver were also collected to quantify the mRNA levels of several genes. The brain was regionally dissected to isolate the hypothalamus and the pre-optic area (POA) as per Bernier et al (Bernier et al, 2008). All tissues were immediately frozen in liquid nitrogen and stored at -80°C for future analysis.…”
Section: Experimental Design Experiments 1: Effects Of Chronic Hypoxiamentioning
confidence: 99%
“…Analyses were performed on 1l of the diluted cDNA [further dilution 1/25 for elongation factor 1-alpha (EF1) and 1/4 for POMC] using the ABsolute TM qPCR SYBR ® Green Mix (Abgene, Cambridge, UK), in a total PCR reaction volume of 15l, containing 50 to 500nmoll -1 of each primer. GK (Panserat et al, 2000), POMC1 (Leder and Silverstein, 2006), EF1 (Bernier et al, 2008) and CRF (Bernier et al, 2008) qPCRs were performed using primers previously described. Primers for NPY were designed according to the available sequence in public databases (GenBank accession number NM_001124266).…”
Section: Gene Expression Analysis By Real-time Quantitative Reverse Tmentioning
confidence: 99%
“…The changes in the activity of glucosensor systems, as well as in the food intake response, might be related to an altered expression of orexigenic or anorexigenic factors in the same areas owing to the interaction between different glycaemic conditions and stress. Several studies have reported changes in the expression of peptides in several brain areas when fish were exposed to stress conditions such as decreased corticotrophin-releasing factor (CRF) and increased NPY expression in the preoptic area of goldfish (Bernier et al, 2004), increased CRF expression in the forebrain (Bernier and Craig, 2005) and preoptic area (Bernier et al, 2008) of rainbow trout and decreased POMC expression in the brain of sole Solea solea (Palermo et al, 2008). However, there are no studies available in the literature regarding changes in the expression of the same peptides under different glycaemic conditions when fish are simultaneously exposed to a stressful situation.…”
Section: Introductionmentioning
confidence: 99%